THE INFLUENCE OF PROMOTIONAL STRATEGIES AND CONSUMER BUYING INTEREST ON PURCHASING DECISIONS AT LOTTE MART MARVELL CITY SURABAYA - Fitri Ayu Ariyani; Abu Darim; Aisyah Darti Megasari; Siswanto Siswanto; Devangga Putra Adhitya Pratama (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study aims to describe the effect of promotion and consumer buying interest on purchasing decisions at Lotte Mart Marvell City Surabaya. The population and sample of this research are HRD and Consumers of Lotte Mart Marvell City. Data collection techniques used are interviews and documentation. The data analysis technique used is descriptive quantitative analysis technique. In quantitative descriptive analysis, instrument test, classical assumption test, and multiple linear regression analysis were carried out. The results of this study are, the f test has a significance value of 0.000. This value is smaller than 0.05 (0.000 <0.05. The f test results are declared feasible because they are less than 0.05 (5%). The results of the t-test value on the promotion variable (X1) are 0.000. This value is smaller than 0.05 (partially influential) and the t-count value proved positive at 3.610. It can be concluded from the two hypotheses, namely H1: